Immunomodulatory activity of Terminalia chebula against Salmonella typhimurium in mice - Khan, K.H. (Recent Research in Science and Technology, 2009)
Typhoid is a world wide problem today due to the emergence of multidrug resistance Salmonella typhi and limited scope of vaccine against this disease. As the plant product has little side effects and is the source of many compounds having wide range of biological activities, diverted the author to study the protective role of Terminalia chebula, against Salmonella typhimurium. The author has already reported the protective effect of aqueous extract of the fruits of this plant against S. typhimurium in vitro as well as in vivo and also the antioxidant activity against these bacteria. In this study the same extract was evaluated for its immunomodulatory activity against S. typhimurium in vivo. Animals pretreated with the same extract at a dose 500 mg/kg body wt orally showed an increase in WBC count by 3x103/cu mm and lymphocyte count by 4 % as compared to saline treated control challenged with 50000 colony forming unit of S. typhimurium. The drug showed the proliferation of lymphocyte by 102% and increase in food pad thickness by 28.87% as compared to infected control in delayed type of hypersensitivity test. Thus the drugs showed its protective effect through its immunomodulatory activity in mice and can be used in typhoid.